Communication methods for aflatoxin management among farmers to facilitate food security in southwest, Nigeria - Alabi, Tiwalola; Okubena, Babatunde; Atilade, Bukunmi; Sabiyi, Abimbola; Hambly, Helen (Frontiers in Communication, 2026)
PurposeFood security is a critical global concern, particularly in Africa where chronic hunger persists. Grain legumes are essential for nutrition but face threats like aflatoxin contamination. This study explores how communication methods influence the knowledge, attitudes, and practices (KAP) of grain legume farmers in managing aflatoxin in Southwest Nigeria.MethodologyThe study employed the Modified Delphi Method, Focus Group Discussions, and Photovoice. The Delphi process involved two rounds of interviews, with eight participants in round one (N = 8) and seven in round two (N = 7). In addition, three focus group discussions were held, comprising 13 participants in the first group, 12 in the second, and 10 in the third. The study also included two participants in the Photovoice component (N = 2). Data were thematically analyzed using NVivo software.FindingsFarmers’ knowledge of aflatoxin management is closely linked to their exposure to training. Although they show a positive attitude and willingness to use products like Aflasafe, its high cost remains a major barrier. Effective communication approaches include demonstrations, training of trainers (ToT), and peer-to-peer learning. The study further identifies media gaps, weak agenda-setting around aflatoxin, and the importance of how messages are framed.Practical implicationsImproving communication strategies and reducing the cost of Aflasafe can enhance adoption and food safety. Participatory and visually oriented communication methods were found to be especially effective in improving behavioral uptake of aflatoxin management.Theoretical implicationsThe study extends the KAP model by emphasizing the role of communication and economic factors in shaping farmer behavior. It draws on communication and behavior change theories, including Diffusion of Innovations, agenda-setting, framing, and media functions, to explain how farmers’ KAP are shaped by communication content, channels, and gaps.Originality/valueThis research offers new insights into aflatoxin management communication in Nigeria, contributing to food security efforts across Africa.